Scenario Planning for Balfour Beatty Rail- Looking Ahead to the Unforeseen Future - Wijaya, Jessica Fidelia (2012)
The aim of this report is to provide Balfour Beatty Rail with long-term scenarios which envision the world, particularly Southeast Asia, in twenty years’ time frame. Southeast Asia is chosen as the geographical scope in line with the group project which produces research about market entry strategy in Indonesia, Thailand, and Vietnam; all of which located in Southeast Asia region. The use of scenarios is meant to reduce the risks of investing, and to capture new business opportunities in the region. This report begins by providing introduction to scenario planning; its definitions, origins, why it is useful for strategic planning, and its strengths and weaknesses. The following chapters of the report will provide explanation of why scenario planning would be useful for Balfour Beatty Rail, the step-by-step process to do scenario planning; including the description of best and worst case scenarios in Southeast Asian railway industry and recommendations to each scenario in the form of strategic action plans. The report concludes that scenario planning is not about getting the future right, but about making better decisions today and improving the quality of strategic thinking. I have experienced this myself as building scenarios has challenged me to ‘think out of the box’ and unfold new perspectives and insights about where the world is heading.